2017
DOI: 10.1093/molbev/msx141
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Genes Are Enriched in Regions of Reduced Archaic Ancestry

Abstract: About 1-6% of the genetic ancestry of modern humans today originates from admixture with archaic humans. It has recently been shown that autosomal genomic regions with a reduced proportion of Neanderthal and Denisovan ancestries are significantly enriched in genes that are more expressed in testis than in other tissues. To determine whether a cellular segregation pattern would exist, we combined maps of archaic introgression with a cross-analysis of three transcriptomic datasets deciphering the transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 39 publications
1
36
0
1
Order By: Relevance
“…In most cases, archaic variants were selected against, with regions of higher selective constraint being depleted in archaic ancestry, particular those that are X-linked or contain testis-expressed and meiotic-related genes. 1,2,16 Some studies have also suggested that Neanderthals had a reduced effective population size, 6,7 owing to a prolonged bottleneck or a deeply structured population. 6,17,18 Natural selection in Neanderthals would thus have been less efficient to purge deleterious mutations, 19,20 a large proportion of which were removed from the genome of modern humans following their admixture with Neanderthals.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, archaic variants were selected against, with regions of higher selective constraint being depleted in archaic ancestry, particular those that are X-linked or contain testis-expressed and meiotic-related genes. 1,2,16 Some studies have also suggested that Neanderthals had a reduced effective population size, 6,7 owing to a prolonged bottleneck or a deeply structured population. 6,17,18 Natural selection in Neanderthals would thus have been less efficient to purge deleterious mutations, 19,20 a large proportion of which were removed from the genome of modern humans following their admixture with Neanderthals.…”
Section: Introductionmentioning
confidence: 99%
“…This is also true for the autosomal regions deficient in both Neanderthal and Denisovan ancestries, which contain a significant enrichment of genes transcribed in meiotic germ cells (Jégou et al, 2017). The phenotypic traits and the type of selective regime acting on them are summarized in Figure 2, and their corresponding genomic regions are listed in Supporting Table. Taking into account that there has been strong selection against archaic introgression among protein-coding genes (Fu et al, 2016;Sankararaman et al, 2016;Vernot & Akey, 2014), functional regions contributing to the uniqueness of some modern human traits could be identified if they are strongly depleted of archaic ancestry .…”
Section: Selection Against Introgressed Regions At the Level Of Genommentioning
confidence: 91%
“…Two biological explanations have been proposed to explain the dynamics of purifying selection on archaic human tracts. Two studies [22,26] found enrichments for testis-expressed and meiotic genes in regions of low Neanderthal ancestry, as well as significantly lower Neanderthal ancestry in the X-chromosome than in the autosomes. Similar observations have been reported for regions of low Denisovan ancestry as well [23] .…”
Section: Admixture and Purifying Selectionmentioning
confidence: 99%